DIAGNOSTICS OF ENTERPRISE LOGISTIC ACTIVITY (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The main theoretical and methodological provisions of diagnostics of enterprise logistic activity as a tool of management process are investigated, it provides timely response to problems in organization of the enterprise logistics system and creation of preconditions for increasing the efficiency of its logistic activity. The mechanism of diagnostics of enterprise logistic activity in the form of a complex system, which integrates indicators, methods, special measures and procedures of research of its results in the conditions of various influence factors is proposed, is based on the basic principles of economic diagnostics and aims at achieving the goals of diagnostics. The essence of the main components of the diagnostic mechanism of enterprise logistic activity is revealed, their variety, interdependence and peculiarities of application are shown, that provides complexity and consistency in the study of a wide range of issues of organization and operation of the enterprise logistics system, as well as in evaluating the effectiveness of logistic solutions.
Keywords: diagnostics, logistic activity, enterprise, diagnostic mechanism, influence factors, indicators, diagnostic methods.